HUBUNGAN PENINGKATAN LAJU ENDAP DARAH (LED) DENGAN JUMLAH LEUKOSIT PADA PASIEN APENDISITIS INFILTRAT DI RSUD Dr. H. ABDUL MOELOEK BANDAR LAMPUNG TAHUN 2010 - 2014 - Wirawan Anggorotomo; Tessa Sjahriani; Masroni Masroni (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2019)
Background: Diabetes Mellitus (DM) is a group of metabolic diseases characterized by an abnormality of insulin secretion, insulin work, or both. DM cases in Indonesia as many as 8,5 million cases in 2013. Prevalence based on diagnosis or symptoms according to the health departement of 2,1%.Purpose: To know the correlation of type 2 diabetes mellitus on triglyceride levels and blood pressureMethods: This study used secondary data derived from the medical record status of patients with diabetes mellitus. The method used is analytic observational with cross sectional approach. Sampling technique using purposive sampling. The population of this study is the diabetes mellitus type 2 in 2017 as many as 151. Sample of 109 respondents. Data analyzed by univariate and bivariate using Chi Square analysis.Results: The frequency of respondent characteristic on female gender as much 57,8%, based on age group >45 old counted 58,7%. Blood pressure frequency distribution found hypertension as much 63,3%. High frequency distribution of triglyceride levels is 67,9%. The Chi Square analysis result there is a significant correlation of type 2 diabetes mellitus on triglyceride levels and blood pressure with Odds Ratio 6,865 with p-value of 0,009.